Distance Learning: The Effectiveness Studies In College Students - Rahmat Solihin; M. Tamsil` Muin; Muhammad Iqbal (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
Distance Learning is learning using a medium that allows interaction between teachers and learners even if they are not in the same place. In its implementation, there are several problems when distance learning is implemented. With some of these problems, distance learning is very interesting to research how effective it is in learning. The type of research used is field research using quantitative approach, while the subject in this study is pgmi study program student at STAI Asy-Syukriyyah Tangerang. Based on the findings in the study, especially in the research subject, students of PGMI study program, showed that the implementation of distance learning in STAI Asy-Syukriyyah Tangerang, categorized as effective with an effectiveness level of 63.79%.